The effectiveness of extra-scrotal fixation following manual detorsion for testicular torsion: a pilot study in a rabbit model - (:unkn) unknown (POLISH UROLOGICAL ASSOC, 2016)
Introduction To investigate the effectiveness of manual detorsion (MD) and applicability of extra-scrotal fixation for testicular torsion in a rabbit model. Material and methods Twelve New Zealand male rabbits were randomized into six groups of two rabbits each. A single-side testicular torsion (TT) model (different degrees, time and sides) was performed in all groups except the Sham group. The groups included: Group 1 (180 degrees; 4 h), Group 2 (720 degrees; 6 h), Group 3 (1080 degrees; 9 h), Group 4 (540 degrees; 1 h), Group 5 (900 degrees; 2 h), and Group 6 (sham-only). Testes were examined by another urologist and radiologist with Color Doppler Ultrasonography (CDU). MD was performed with CDU until blood flow was observed in the affected testis. Extra-scrotal fixation was then conducted in these animals. The testes were then harvested for blinded histopathological examinations. Results TT was detected in all animals except the control group. The CDU examination detected decreased blood flow only in Group 1. An opposite rate was observed between the spermatic cord diameter and torsion degree. A wrong direction of MD in the first step was observed in two rabbits in Groups 4 and 5. Torsion signs were observed only in Group 3. Rest torsion was observed in Groups 3 and 5 after extra-scrotal fixation. Histopathological examinations showed that testicular damage increased in parallel to torsion duration. Conclusions Extra-scrotal fixation after MD along with CDU may be a simple and minimally invasive treatment option in TT therapy. However, this must be verified with further studies.
Keywords: extra-scrotal fixation; Doppler ultrasonography; manual detorsion; scrotal exploration; testicular torsion; SPERMATIC CORD; DOPPLER ULTRASOUND